Dual-tDCS Enhances Online Motor Skill Learning and Long-Term Retention in Chronic Stroke Patients - Lefebvre, Stéphanie; Laloux, Patrice; Peeters, André; Desfontaines, Philippe; Jamart, Jacques; Vandermeeren, Yves (Frontiers in Human Neuroscience, 2013)
Background Since motor learning is a key component for stroke recovery, enhancing motor skill learning is a crucial challenge for neurorehabilitation. Transcranial direct current stimulation (tDCS) is a promising approach for improving motor learning. The aim of this trial was to test the hypothesis that dual-tDCS applied bilaterally over the primary motor cortices (M1) improves online motor skill learning with the paretic hand and its long-term retention. Methods Eighteen chronic stroke patients participated in a randomised, cross-over, placebo-controlled, double bind trial. During separate sessions, dual-tDCS or sham dual-tDCS was applied over 30 min while stroke patients learned a complex visuomotor skill with the paretic hand: using a computer mouse to move a pointer along a complex circuit as quickly and accurately as possible. A learning index involving the evolution of the speed/accuracy trade-off was calculated. Performance of the motor skill was measured at baseline, after intervention and one week later. Results After sham dual-tDCS, eight patients showed worsening performance. In contrast, dual-tDCS enhanced the amount and speed of online motor skill learning compared to sham (p < 0.001) in all patients; this superiority was maintained throughout the hour following. The speed/accuracy trade-off was shifted more consistently after dual-tDCS (n=10) than after sham (n=3). More importantly, one week later, online enhancement under dual-tDCS had translated into superior long-term retention (+44%) compared to sham (+4%). The improvement generalised to a new untrained circuit and to digital dexterity. Conclusion A single session of dual-tDCS, applied while stroke patients trained with the paretic hand significantly enhanced online motor skill learning both quantitatively and qualitatively, leading to successful long-term retention and generalisation. The combination of motor skill learning and dual-tDCS is promising for improving post-stroke neurorehabilitation